2017
DOI: 10.3390/w9090693
|View full text |Cite
|
Sign up to set email alerts
|

Model and Growth Stage Based Variability of the Irrigation Demand of Onion Crops with Predicted Climate Change

Abstract: Predicted climate change will affect agricultural water resources. Particularly vegetable crops will be concerned due to high water demand and high vulnerability to water scarcity. Present vegetable production already requires irrigation water. To assess future irrigation demand, the impact of climate change needs to be revealed region-and crop-specifically. For robust predictions, a wide range of scenarios has to be simulated using different climate models. The aim of this study is to identify the climate cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Predicted climate change and global warming have resulted in the emergence of extreme weather events viz. erratic precipitation patterns leading to drought and floods, temperature extremes and soil salinity that act as the major constraint for agricultural productivity particularly the vegetable crops (Schmidt and Zinkernagel, 2017). Drought is one of the major abiotic stress that adversely influences growth and yield of economically important crops.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
“…Predicted climate change and global warming have resulted in the emergence of extreme weather events viz. erratic precipitation patterns leading to drought and floods, temperature extremes and soil salinity that act as the major constraint for agricultural productivity particularly the vegetable crops (Schmidt and Zinkernagel, 2017). Drought is one of the major abiotic stress that adversely influences growth and yield of economically important crops.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%
“…In several studies, the total antioxidant capacity, total phenolic content and also phenolic and antioxidant active compounds in hazelnut have been reported (Altun et al 2013;Arcan and Yemenicioğlu, 2009;Li and Parry, 2011). The irrigation influences the quality and quantity of product in agriculture (Schmidt and Zinkernagel, 2017). It has been shown that, the irrigation application enhanced the kernel growth and quantity of hazelnut (Cristofori et al, 2014;Külahçılar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Differences due to the Climate data temporal scale, K c and Land cover map scenarios show that uncertainty associated with precipitation, evapotranspiration, plant factors and land classification schemes affect modelling outcomes. These factors have also been recognized as key variables affecting relevant ecosystem services in other studies [24,93,94]. A critical and interesting result of this study was from the Climate data temporal scale scenario which showed that ignoring distinctive wet and dry seasons by using an annual model are likely to produce model outputs that are less likely to reflect true values.…”
Section: Impact Of Uncertainty On Water Provisionmentioning
confidence: 77%